PENGARUH LATIHAN MUSICAL BALL TERHADAP KETERAMPILAN DRIBBLING TIM SSB CHEVRON U-15 RUMBAI - Rizki Chandra Putra; zainur Zainur; Ni Putu Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Dribbling techniques are very important in football sports, but from the author's observation and also information from the coach, that there are shortcomings and weaknesses that are contained in the technical factors in these players, especially when dribbling. This study aims to determine the effect of musical ball practice on dribbling skills in the Chevron U-15 Rumbai players. The population in this study were all SSB U-15 players Chefron Rumbai consisting of 16 people. sampling technique in this study is total sampling. The test is done by dribbling the ball through the stakes that have been determined the distance. The purpose of the dribbling test is to measure dribbling skills quickly with changes in direction. The data analysis technique uses the t-test. Based on the t-test yielding tcount of 2.595 with ttable 1.753, it is rejected, at the alpha level (0.05. It can be concluded that there is an influence of musical ball training on dribbling skills on SSB U-15 players Chefron Rumbai. Based on the above results, it can It was concluded that there was an influence of musical ball practice on dribbling skills on SSB U-15 players Chefron Rumbai, meaning that practicing musical ball can be used to improve dribbling skills.Key Words: Musical Ball, Dribbling Skills